Transformasi Minat Akuntan Publik: Artificial Intelligence, Workplace Well-Being & Pertimbangan Pasar Kerja - Sri Lestari Yuli Prastyatini; Uum Helmina Chaerunisak; Erliana Vika Maharani (Jurnal Riset Akuntansi, 2026)
In Indonesia, interest in becoming a public accountant is very low. Several factors prevent accounting graduates from choosing public accounting as their career choice. This phenomenon is the reason for this study. This study aims to reconstruct the understanding of career interest as a public accountant, by considering the integrative influence of AI, workplace well-being, and labor market considerations. A quantitative approach was used by distributing questionnaires to accounting students at various universities in Yogyakarta as a representation of the future generation of prospective public accountants. Data analysis was conducted using IBM SPSS Statistics 26. The results show that artificial intelligence, workplace well-being, and labor market considerations have a positive and significant influence on career interest as a public accountant. The addition of the artificial intelligence variable is the main difference between this study and previous studies. This research provides a theoretical contribution through the integration of technological, psychological, and economic dimensions in the analysis of public accountant career behavior. Practically, the results of this study provide strategic recommendations for Public Accounting Firms and educational institutions to design work environments and curricula that are responsive to the values of the digital generation, particularly in preparing adaptive accounting talent in the era of automation.